Defining of medical and psychological assistance volume to women with physiological pregnancy - Bozhuk, O. (Journal of Education, Health and Sport, 2015)
Bozhuk O. Defining of medical and psychological assistance volume to women with physiological pregnancy. Journal of Education, Health and Sport. 2015;5(5):86-100. ISSN 2391-8306. DOI 10.5281/zenodo.17453 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A86-100 https://pbn.nauka.gov.pl/works/559169 http://dx.doi.org/10.5281/zenodo.17453 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Defining of medical and psychological assistance volume to women with physiological pregnancy O. Bozhuk National Medical University named after O. O. Bohomolets Department of General and Medical Psychology and Pedagogy Summary. Mother and prenate are in close symbiotic relationship, which manifests itself in the interaction at physiological and psychological levels of organisms’ functioning. Reflexive accepting yourself as a pregnant woman depends also on the the motives of conception, planed / not planed parenthood, social situation and level of psychological and social support. The aim of the research is to determine the volume and structure of medical and psychological assistance. The research was conducted in maternity hospital prenatal consultation centre of Chernihiv City Council and Municipal nonprofit company "Consultation and Diagnostic Center" of Golosiivsky district in Kyiv in 2010-2014. The research involved 185 pregnant women whose age ranged from 17 to 36 years old (group 1 μ = 25,5 ± 0,27, group 2 -μ = 24,8 ± 0,27). Women of group 1 show some fear of future childbirth, which applies to both the woman herself and the unborn child. The course of psychological education was developed for women of group 1, which included not only the educational part regarding the physiology of pregnancy and childbirth, postpartum, etc. but also the part aimed at reducing anxiety and overcoming identified fears. For the women of group 2 psychological influence is required in all researched spheres (personal, psycho-social, psycho-emotional and reproductive) if the fear of future birth is present and vivid. According to conducted research for women of group 2 there were found the next targets of psycho-therapeutic influence which have been taken into account when developing the course of psycho- correction: to normalize psycho-emotional state of the pregnant woman, to reduce anxiety level; to work with identified fears; to normalize emotional relation in the dyad "prenate - mother" and creating the triad "father-mother-prenate"; to normalize family relations and to construct optimal types of family systems; to harmonize personal traits of the pregnant woman. Based on the results of the study proved the need for medical and psychological support to women with physiological pregnancy. Keywords: pregnancy, psychoeducation, psycho-correction, psychotherapeutics target, reproductive motivation.